Characterization of Alginate/Silver Nanobiocomposites Synthesized by Solution Plasma Process and Their Antimicrobial Properties. (22nd February 2016) - Nam, Sangwoo; MubarakAli, D.; Kim, Jungwan
Abstract : Solution plasma process (SPP) was adopted to prepare alginate/silver nanoparticle (AL/AgNP) biocomposites. The biocomposites were synthesized in solutions of varying concentrations of AgNO3 (1−5 mM) and alginate (0.1−0.3%, w/w) by discharging plasma for 7 min at 800 V with 30 kHz frequency using a pulsed unipolar power supply. The AL/AgNP emulsion was fabricated into 3D scaffolds by freeze drying and lyophilization and then stabilized by cross-linking via UV irradiation. UV-Vis spectroscopy of the biocomposites showed a characteristic absorbance at the maximum of 415–440 nm with increase in the intensity of the peaks as the concentration of AgNO3 increased. FE-SEM analysis showed that the 3D scaffolds had microporous structures with fine and uniform pores of 3–9 ± 2.0  μ m in diameter. TEM analysis revealed that AgNPs in the biocomposites were in spherical shape with size range of 5–40 ± 2.0  nm (AL0.3/Ag5) and well distributed in the matrix. The AL/AgNP biocomposites showed microbicidal activity against 9 human pathogens with MIC of 9.6–21  μ g/mL for bacteria and 85–425  μ g/mL for fungi. Almost all of the E. coli cells (99.8%) were killed by the treatment with 42.5  μ g/mL of AgNPs at room temperature for 1 h.